ANALISIS KEMAMPUAN MENULIS TEKS NARASI BERDASARKAN STRUKTUR DAN KAIDAH KEBAHASAAN PADA SISWA KELAS IV SD NEGERI 3 BUNUTIN - Ni Wayan Eka Julianti; Nurul Isnaini Fitriyana; Ni Wayan Sri Darmayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze narrative text writing ability based on structural elements and linguistic features, as well as to identify the influencing factors among fourth-grade students at SD Negeri 3 Bunutin. This study applied a descriptive qualitative research approach. The research subjects comprised 12 fourth-grade students of SD Negeri 3 Bunutin during the even semester of the 2025/2026 academic year. Data were gathered through interviews, observations, and documentation of students' narrative writing artifacts. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldana, involving data reduction, data display, and conclusion drawing. The findings revealed that students' narrative writing abilities were categorized into varying levels. Based on core indicators (content, orientation, complication, resolution, and linguistic features), 6 students (50%) achieved the good category, 4 students (33.3%) fair, and 2 students (16.7%) poor. All students (100%) successfully generated story ideas relevant to the given theme. Regarding text structure, 100% of students composed the orientation, 83.3% included complications, and 66.7% provided resolutions. In terms of linguistic features, the primary challenges identified were limited vocabulary usage, capitalization errors, and improper punctuation (periods and commas). Internal factors influencing writing skills included interest, motivation, and basic reading skills, whereas external factors encompassed teaching methods, instructional media utilization (such as series pictures), classroom environment, writing practice frequency, and individual teacher guidance. Keywords: keyword 1, keyword 2, keyword 3.